2023
DOI: 10.1002/cbdv.202300222
|View full text |Cite
|
Sign up to set email alerts
|

Monocarbonyl Analogs of Curcumin with Potential to Treat Colorectal Cancer

Abstract: Curcumin has a plethora of biological properties, making this compound potentially effective in the treatment of several diseases, including cancer. However, curcumin clinical use is compromised by its poor pharmacokinetics, being crucial to find novel analogs with better pharmacokinetic and pharmacological properties. Here, we aimed to evaluate the stability, bioavailability and pharmacokinetic profiles of monocarbonyl analogs of curcumin. A small library of monocarbonyl analogs of curcumin 1a-q was synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Curcumin had a lipophilicity value of 3.2, which clearly indicates that curcumin falls within the moderately lipophilic range [ 37 , 38 ]. Interestingly, this reporting is in line with the experimental data previously reported by Clariano et al (2023) [ 39 ] and Shereen et al (2019) [ 40 ], who evaluated the mechanistic delivery of curcumin in humans and estimated the lipophilicity of curcumin to be in a similar range (~LogP 3.6). The synthetic derivatives 1A6 and 1B8 demonstrated a higher lipophilicity than curcumin, potentially indicating improved membrane permeability which is advantageous for drug development to enhance bioavailability.…”
Section: Discussionsupporting
confidence: 90%
“…Curcumin had a lipophilicity value of 3.2, which clearly indicates that curcumin falls within the moderately lipophilic range [ 37 , 38 ]. Interestingly, this reporting is in line with the experimental data previously reported by Clariano et al (2023) [ 39 ] and Shereen et al (2019) [ 40 ], who evaluated the mechanistic delivery of curcumin in humans and estimated the lipophilicity of curcumin to be in a similar range (~LogP 3.6). The synthetic derivatives 1A6 and 1B8 demonstrated a higher lipophilicity than curcumin, potentially indicating improved membrane permeability which is advantageous for drug development to enhance bioavailability.…”
Section: Discussionsupporting
confidence: 90%
“…In some methodologies, at the end of the reaction, the reaction mixture is neutralized by adding a hydrochloric acid (HCl) solution to the vessel [21] In most cases, the resulting solid is separated from the reaction mixture by vacuum filtration and washed with ice water, to remove excess base. Finally, the solid product is dried and recrystallized from hexane/ethyl acetate, EtOH, or EtOH/ to obtain pure crystals [16,[21][22][23][24]. Besides NaOH, calcium hydroxide (Ca(OH)2) has been used as a basic catalyst in CSC to obtain MKCs.…”
Section: Base-catalyzed Claisen-schmidt Condensationmentioning
confidence: 99%
“…Besides that, all the tested compounds proved to be more stable in PBS (phosphate buffer saline) with 20% acetonitrile at 37 o C for 48 h than curcumin and obeyed the 'drug-likeness properties. The authors identified MKC 26 as the most promising antitumoral compound, with an IC50 of 1.95 μM [21].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Among different approaches, the synthesis of novel curcumin analogues by molecular modifications has exhibited similar anti-potent effects to the original curcumin molecules but with better stability and bioavailability, which are ideal for further development into novel drugs [ 42 ]. While the basic molecular structure of curcumin comprises two phenol groups connected by two α, β unsaturated carbonyl groups, a variety of curcumin analogues have been developed by modifying functional moieties, such as biaryl rings, diketone and diene chain, onto different positions of the original curcumin structure [ 36 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. With these modifications, curcumin analogues are superior to curcumin in term of pharmacokinetic properties, chemical stability and anti-cancer activities [ 46 , 52 , 53 , 54 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…comprises two phenol groups connected by two α, β unsaturated carbonyl groups, a variety of curcumin analogues have been developed by modifying functional moieties, such as biaryl rings, diketone and diene chain, onto different positions of the original curcumin structure [36,[43][44][45][46][47][48][49][50][51]. With these modifications, curcumin analogues are superior to curcumin in term of pharmacokinetic properties, chemical stability and anti-cancer activities [46,[52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%